Studi Eksperimental Pengaruh Abu Serbuk Kayu dengan Bakteri Bacillus Subtilis Sebagai Bahan Stabilisasi Tanah Lunak Terhadap Nilai Proctor Test Tanah Lunak di Kecamatan Wonoayu - Sidoarjo - Mufid Afif Syafriansah; Laily Endah Fatmawati (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to examine the effect of wood ash and the combination of wood ash with Bacillus subtilis as soil stabilizing agents on the compaction value (Proctor Test) and unconfined compressive strength (UCS) of soft clay soil. Soil samples were collected from Ploso Village, Wonoayu District, Sidoarjo Regency, which is characterized by high-plasticity organic clay with low bearing capacity. The test results revealed that the addition of wood ash increased the maximum dry density (MDD) from 1.446 gr/cm³ in natural soil to 2.036 gr/cm³ at 15% mixture, while the optimum moisture content (OMC) decreased from 27% to 20%. UCS also improved from 0.29981 kg/cm² in natural soil to 0.523213 kg/cm² at 15% mixture. Furthermore, the combination of wood ash with 5% Bacillus subtilis produced more significant results, with MDD reaching 2.047 gr/cm³, OMC reduced to 22%, and UCS increasing to 0.66386 kg/cm². These findings confirm that wood ash is effective as an eco-friendly stabilizing material, and its combination with Bacillus subtilis can further enhance the physical and mechanical properties of soft clay soil.